Obesity, Cardiorespiratory Fitness, and Self-Reported Sleep Patterns in Chilean School-Aged Children - Garcia-Hermoso, A (Routledge, 2017)
The aims were to examine the association of sleep patterns with being overweight or obese and to analyze the association of cardiorespiratory fitness (CRF) with sleep patterns in children. The study involved 395 schoolchildren (12–13 years old). Sleep patterns were assessed with the Sleep Self-Report (SSR) questionnaire, grouped into four subscales: sleep quality, sleep-related anxiety, bedtime refusal, and sleep routines. CRF was predicted by the 20-m shuttle-run test. Logistic regression models showed that sleep-related anxiety problems predicted being overweight or obese in both sexes, and sleep quality problems predicted being overweight or obese in girls. Also, girls who had better CRF levels were less susceptible to sleep-related anxiety problems. Studies are required to determine if increasing CRF could be a possible strategy for improving sleep quality. Copyright © Taylor & Francis Group, LLC.